PEMBERIAN LIMBAH PADAT PABRIK KELAPA SAWIT DAN PUPUK FOSFOR PADA TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) BELUM MENGHASILKAN - Gultom, Adri Naldi; Ariani, Erlida (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to determine the effect of the interaction of the provision of solid waste PKS and manure and to get the best treatment on the growth of immature oil palm trees. This research has been conductedat the Experimental Farm, Faculty of Agriculture, University of Riau from March to June 2016. This research arranged experimentaly by using Block Randomized Design (BRD) consisting of 2. The first factor is the aplication of solid waste PKS comprising: a dose of solid waste PKS 0 kg / plants, 10 kg / plant, and 15 kg / plant. The second factor is the aplication of phosphorus fertilizer comprising: a dose of fertilizer P 0 kg / plant, 0,5 kg / plant, and 0,6 kg / plant. Of the two factors obtained 9 combination treatment and each treatment was repeated 3 times, so there are 27 experimental units. Data were analyzed statistically and continued using DNMRT at 5% level. Parameters measured were increase of height, increase the number of midrib, the width of the leaf, and the length of the leaf. The result showed that the interaction of solid waste administration PKS and fertilizer P gives no real effect on all parameters except as height. The aplication of solid waste MCC dose of 15 kg / plant and P fertilizer dosage of 0,5 kg / plant is the best treatment to the growth of oil palm plantation immature. Keywords : Palm Oil Plant, Solid Waste MCC, Phosphorus.